Leadership styles of technical directors and job satisfaction of employees: a study conducted in PSSI's of the Districts of Guarda and Viseu - Pereira, Susana (2016)
Introduction: This work is a quantitative, transversal, descriptive and correlational study. Objectivos: The main purpose of the present study was to understand the collaborators perspective of the relationship between the leadership styles used by technical directors and job satisfaction of employees in nine Private Social Solidarity Institutions (PSSI,) in the districts of Guarda and Viseu, taking also into account the relevance of sociodemographic and professional variables in the field of job satisfaction. Methods: The sample consists of 85 employees and the data collection instrument integrates questions of socio-demographic and professional characterization and two validated scales for assessing: i) the degree of job satisfaction in various dimensions (developed by Instituto da Segurança Social, 2007) and ii) the leadership style of the technical directors (developed by Melo, 2004), according to the perception of employees. Results: The results indicate that the relational leadership style promotes greater satisfaction and the leadership focused on task induces lower satisfaction. Conclusions: The hypothesis under study allows to conclude that variables: gender, type of work contract, service time and qualifications influence employee’s job satisfaction.